Prevalence of metabolic syndrome in female patients with rheumatoid arthritis in Erbil city - Abbas Othman, Mustafa; Qader Meena , Mohammed (Diyala Journal of Medicine, 2023)
Background: Rheumatoid arthritis and metabolic syndrome are closely linked, which considerably raises the risk of cardiovascular complications, and consequently, morbidity and mortality. Treatment of the metabolic syndrome reduces mortality and morbidity of cardiovascular disease. Objective: To assess the prevalence of metabolic syndrome in a population of female patients with Rheumatoid arthritis, and association with comorbidities and Disease-modifying anti-rheumatic drugs (DMARDs). Patients and Methods: This cross-sectional analytic study was conducted in Erbil City. A total of 110 female patients with the diagnosis of rheumatoid arthritis were included during the period of July 2021-March 2022. Anthropometric indices, blood pressure, fasting blood sugar, lipid profile, and proteinuria were investigated. The metabolic syndrome defining criteria from the international diabetes federation (IDF-2005) were applied. Results: Out of 110 patients with rheumatoid arthritis, 63 (57.3%) were found to have metabolic syndrome, in whom the majority of them 52 (71.2%) were obese class 1. A significant association of metabolic syndrome was found with comorbidities (hypertension, diabetes, and hypothyroidism), p-value 0.019, and TNF-alpha inhibitor drugs were shown to be associated with a reduced risk for metabolic syndrome. Conclusion: Metabolic syndrome is common in rheumatoid arthritis patients, and it increases the risk of other comorbidities (hypertension, diabetes, and hypothyroidism) as well as cardiovascular diseases. Patients on biologic disease modifying anti-rheumatic drugs are at a lower risk of metabolic syndrome.